Evaluation of Resistance in Brinjal (Solanum melongena L.) against Brinjal Shoot and Fruit Borer (Leucinodes orbonalis Guen.) Infestation: A Review - Abdullah Shaukat, Muhammad; Ahmad, Ammad; Mustafa, Farwa (International Journal of Applied Sciences and Biotechnology, 2018)
Brinjal or eggplant (Solanum melongena L.) is widely grown vegetable in South and South-East Asian countries. There are various factors that limits the production of brinjal among which brinjal shoot and fruit borer (Leucinodes orbonalis Guen) is the most common one which occurs during the time at all the phases of the crop development. The damage caused by shoot and fruit borer (Leucinodes orbonalis L.) in brinjal begins immediately after transplantation of crop and growers will have to harvest an immature crop. The life cycle of BSFB completes in 19-28 days. It is estimated by various specialists that increase in the number of shoots per plant will lower the attack rate of the pest. Round shape fruits are more susceptible compared to long bodied fruits. It is also examined that total sugar contents increase the attack while total phenol contents produce resistance to pest. The information of nature and relative extent of gene exploit (additive and non-additive) is of key importance in scheming appropriate and well-organized breeding plan for enhancement of resistance and crop yield. Physical and chemical features, for example, plant structure, fruit form, spines of leaves, branches, petioles, calyx of fruits, fruit skin thickness and shoot thickness, synthetic traits, for example, ash, crude fibre, silica, sugars, mineral ingredients, total phenol contents of fruit and shoot of brinjal are examined to be included towards the shoot and fruit borer resistance in brinjal. Int. J. Appl. Sci. Biotechnol. Vol 6(3): 199-206